2020
DOI: 10.1111/dth.13908
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine approach for psoriasis management, time for application? A systematic review of published studies

Abstract: Psoriasis is a common chronic inflammatory skin condition. It has a chronic course with multiple evolving relapses and patients require long-term treatment and followup. Teledermatology was introduced for diagnosis, treatment and follow-up of chronic diseases. Thus, we performed a systematic review for collecting the evidence regarding the efficacy of telemedicine in psoriasis management. Out of 287 records, we included seven studies (four of which were randomized controlled trials). We found that telemedicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
(79 reference statements)
0
14
0
Order By: Relevance
“…Psoriasis is a chronic relapsing disease that requires long-term treatments and frequent follow-ups [ 6 ]. Besides in-person consultations, teledermatology has become an opportunity in daily clinical settings for those who, for any reason, cannot attend the visit and at the same time require medical advice [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Psoriasis is a chronic relapsing disease that requires long-term treatments and frequent follow-ups [ 6 ]. Besides in-person consultations, teledermatology has become an opportunity in daily clinical settings for those who, for any reason, cannot attend the visit and at the same time require medical advice [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Such an idea is in line with Gisondi et al, that supports the use of online consultations for patients with stable psoriasis on maintenance treatment with biological agents, as routine visits usually end up with a confirmation of ongoing treatment—different from naïve or unstable patients who would rather benefit from in-person visits [ 14 ]. Likewise, Dahy et al would encourage face-to-face visits for establishing a diagnosis, and online consultations for the follow-ups [ 6 ]. More applications will be found with the incorporation and implementation of digital platforms in health care systems.…”
Section: Resultsmentioning
confidence: 99%
“…No statistically significant difference was noticed among the study and control groups in all demographic characteristics. (17) . Evidence showed that patients prefer an individualized approach to their treatment; patients want to be seen as a person, not as a psoriasis case.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence about the use of telemedicine for the management of children with psoriasis is limited, while the feasibility of this approach in adults is supported by extensive literature [43][44][45][46][47][48]. A recent survey among pediatric psoriasis patients in France found that during the COVID-19 lockdown, [ 70% of the patients who were visited because of psoriasis did so via telemedicine [49].…”
Section: Telemedicinementioning
confidence: 99%